Purslane (Portulaca oleracea L.) Growth, Nutritional, and Antioxidant Status under Different Nitrogen Levels in Hydroponics - Chrysargyris, Antonios; Xylia, Panayiota; Zengin, Gokhan; Τζωρτζάκης, Νίκος Γ. (My University, 2024)
Purslane (Portulaca oleracea L.) is a common weed that attracts research and agricultural attention because of its significant nutritional value, and it is used commercially. The present work rated the effect of different nitrogen (N) concentrations, i.e., N50: 50 mg L−1; N100: 100 mg L−1; N200: 200 mg L−1; and N300: 300 mg L−1, on the growth, physiology, antioxidant capacity, and nutrient accumulation in the different plant parts of hydroponically grown purslane. Seedlings were transplanted to a Nutrient Film Technique (NFT) system and exposed to different N levels. The plants grown in high N levels of 300 mg L−1 had decreased biomass production, leaf number, leaf stomatal conductance, and total flavonoid content because of the increased oxidative stress, as shown by the elevated lipid peroxidation levels. Several enzymatic (superoxide dismutase) and non-enzymatic (ascorbic acid, total phenolics) plant antioxidant activities were activated to counteract the oxidative factors. Plants grown in intermediate N levels in the NS (i.e., 100 mg L−1) had decreased oxidative stress as several enzymatic antioxidant activities, i.e., peroxidases and catalases, were increased. Additionally, the water use efficiency and nitrogen uptake, as well as leaf stomatal conductance and leaf chlorophyll fluorescence, were increased in plants grown at a N level of 200 mg L−1. The mineral accumulation in the leaves, stems, and roots fluctuated, with increased calcium, magnesium, and sodium content being observed in the plants grown at high N levels in the nutrient solution. The stems accumulated less N compared with the leaves, but the N content and accumulation rates in purslane leaves were not affected by the N levels in the nutrient solution. Therefore, to increase the yield, nutritional value, and water use efficiency of purslane that is grown hydroponically, a concentration of 200 mg L−1 N in the nutrient solution is recommended.
Keywords: nitrogen use efficiency; nutrient uptake; purslane; Soilless culture; translocation factors